Productivity Effects of Air Pollution: Evidence from Professional Soccer - Andreas Lichter; Nico Pestel; Eric Sommer (Institute for the Study of Labor (IZA), 2015)
In this paper, we estimate the causal effect of ambient air pollution on individuals' productivity by using panel data on the universe of professional soccer players in Germany over the period 1999-2011. Combining this data with hourly information on the concentration of particulate matter in spatial proximity to each stadium at the time of kickoff, we exploit exogenous variation in the players' exposure to air pollution due to match scheduling rules that are beyond the control of teams and players. Our analysis shows negative and non-linear effects of air pollution on short-run productivity. We further find that the effect increases with age and is stronger in case players face an additional physical burden.
Keywords: J24; Q51; Q53; 330; air pollution; productivity; soccer; sports data; Germany